Sustainability potential of app-based food loss measurement: Farmers' perspectives in southwestern British Columbia, Canada - Hook, Alexander; Soma, Tammara (Frontiers in Sustainability, 2022)
Food loss is a systemic problem contributing to negative environmental, social, and economic impacts. However, despite food loss quantification being identified as critical for food loss prevention and reduction, there is a dearth of studies exploring opportunities to digitize or simplify food loss measurement. Moreover, post-harvest food loss estimates can be difficult to obtain as farmers grow different types of crops and have diverse technical skills as well as resources. Digital agriculture technologies such as farm management apps that can help farmers accurately record their yield and sales may provide a useful method for quantifying food loss. Accurate food loss quantification may also help provide better baseline measurement for policymakers. To assess the potential role of digital agricultural tools for food loss quantification, this exploratory study recruited seven farmers in southwest British Columbia to test an open access farm management app called LiteFarm for two months and digitally recorded their harvest logs. Drawing upon semi-structured key informant interviews, this study found that time scarcity and crop diversity were barriers to using the app. An unexpected benefit to the app is that it can better inform land use decisions when utilized for pre-harvest planning and therefore may help with loss prevention. Findings from this study highlight farmers' struggles to focus on sustainability and reducing food loss, especially when balancing their economic interests. Inclusive digital technologies and deeper engagement with farmers are needed to develop food loss quantification methods that fit diverse farming contexts.